Hospital patients' reports of medical errors and undesirable events in their health care. Issue 5 (12th June 2012) - Davis, Rachel E.; Sevdalis, Nick; Neale, Graham; Massey, Rachel; Vincent, Charles A.
Abstract: Objective To investigate hospital patients' reports of undesirable events in their health care. Design Cross‐sectional mixed methods design. Participants A total of 80 medical and surgical patients (mean age 58, 56 male). Intervention Patients were interviewed post‐discharge using a survey to assess patient reports of errors or problems in their care. Patients' medical records and notes were also reviewed. Main outcome measures Frequency of health care process problems, medical complications and interpersonal problems, and patient willingness to report an undesirable event in their care. Results In total, 258 undesirable events were reported (rate of 3.2 per person), including 136 interpersonal problems, 90 medical complications and 32 health care process problems. Patients identified a number of events that were reported in the medical records (30 out of 36). In addition, patients reported events that were not recorded in the medical records. Patients were more willing ( P < 0.05) to report undesirable events to a researcher (as in the present case) than to a local or national reporting system. Conclusion Patients appear able to report undesirable events that occur in their health care management over and above those that are recorded in their medical records. However, patients appear more willing to report these incidents for the purpose of a study rather than to an established incident reporting system. Interventions aimed at educating and encouraging patients about incident reporting systems need to be developed in order to enhance this important contribution patients could make to improving patient safety.